Learn more about

Refine search

Results (displaying matches 1-50 of 578) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
1062.a.6372.1 1062.a \(y^2 + (x^3 + 1)y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
2148.a.77328.1 2148.a \(y^2 + (x^3 + x)y = x^4 - 3x^3 + 3x^2 - x\) $\mathrm{USp}(4)$ 1
3456.a.248832.1 3456.a \(y^2 + xy = x^6 + x^4 - 2x^3 - x^2 + x\) $\mathrm{USp}(4)$ 1
3492.a.670464.1 3492.a \(y^2 + (x^3 + 1)y = x^5 - 3x^3 + 3x + 2\) $\mathrm{USp}(4)$ 1
4512.b.324864.1 4512.b \(y^2 + xy = x^6 - 3x^4 + 3x^2 - x\) $\mathrm{USp}(4)$ 1
5532.a.265536.1 5532.a \(y^2 + (x^3 + x^2 + x)y = x^3 - x^2 - x + 1\) $\mathrm{USp}(4)$ 1
6443.a.6443.1 6443.a \(y^2 + y = x^5 - x^4 - 2x^3 + x^2 + x\) $\mathrm{USp}(4)$ 2
6672.a.720576.1 6672.a \(y^2 + xy = 2x^5 - 4x^4 - x^3 + 5x^2 - 2x\) $\mathrm{USp}(4)$ 1
7211.a.7211.1 7211.a \(y^2 + (x^3 + 1)y = -x^4 + 2x^3 - 2x^2\) $\mathrm{USp}(4)$ 2
7403.a.7403.1 7403.a \(y^2 + y = x^5 + x^4 - 2x^3 - x^2 + x\) $\mathrm{USp}(4)$ 2
7445.a.7445.1 7445.a \(y^2 + y = x^5 + 3x^4 + 2x^3\) $\mathrm{USp}(4)$ 2
7627.a.7627.1 7627.a \(y^2 + (x^2 + x + 1)y = x^5 - x^4 - 2x^3\) $\mathrm{USp}(4)$ 2
7877.d.7877.1 7877.d \(y^2 + y = x^5 + 3x^4 - 5x^2 - x + 2\) $\mathrm{USp}(4)$ 2
8864.a.17728.1 8864.a \(y^2 + (x^3 + x^2 + x + 1)y = x^3 - x\) $\mathrm{USp}(4)$ 2
9446.a.18892.1 9446.a \(y^2 + (x^3 + 1)y = x^5 + x^4 - x^2 - x\) $\mathrm{USp}(4)$ 2
9589.b.9589.1 9589.b \(y^2 + y = x^5 - 3x^3 + 2x\) $\mathrm{USp}(4)$ 2
10073.a.10073.1 10073.a \(y^2 + (x^2 + x + 1)y = -x^5 + 2x^4 - 3x^2\) $\mathrm{USp}(4)$ 2
10328.a.20656.1 10328.a \(y^2 + xy = 2x^5 + x^4 - 4x^3 - 2x^2 + 2x + 1\) $\mathrm{USp}(4)$ 2
10681.a.117491.1 10681.a \(y^2 + y = x^5 - 23x^3 + 69x^2 - 77x + 30\) $\mathrm{USp}(4)$ 2
10895.a.54475.1 10895.a \(y^2 + (x^2 + x + 1)y = -x^5 + 2x^4 - 3x^3\) $\mathrm{USp}(4)$ 2
11016.c.793152.1 11016.c \(y^2 + (x + 1)y = x^6 - 3x^4 - 2x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 1
11061.a.33183.1 11061.a \(y^2 + (x^2 + x + 1)y = -x^5 - x^4 + x^2 + x\) $\mathrm{USp}(4)$ 2
11168.a.22336.1 11168.a \(y^2 + y = 2x^5 - 3x^3 + x\) $\mathrm{USp}(4)$ 2
11347.b.11347.1 11347.b \(y^2 + (x^3 + 1)y = x^5 + 3x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 2
11519.a.11519.1 11519.a \(y^2 + (x^2 + x + 1)y = x^5 - 2x^4 + x^3 - 2x^2\) $\mathrm{USp}(4)$ 2
11667.a.105003.1 11667.a \(y^2 + y = x^5 + 2x^4 - x\) $\mathrm{USp}(4)$ 2
11749.a.11749.1 11749.a \(y^2 + y = x^5 - x^4 - x^3 + x^2\) $\mathrm{USp}(4)$ 2
11914.a.548044.1 11914.a \(y^2 + (x^3 + x)y = -2x^4 - x^2 - 5x + 1\) $\mathrm{USp}(4)$ 2
11971.b.11971.1 11971.b \(y^2 + y = x^5 + x^4 - x^3 + x\) $\mathrm{USp}(4)$ 2
12092.a.48368.1 12092.a \(y^2 + (x^2 + 1)y = x^5 - x^4 - 3x^3 + x^2 + 2x\) $\mathrm{USp}(4)$ 2
12761.a.89327.1 12761.a \(y^2 + (x^2 + x + 1)y = x^5 - 5x^3 + 2x^2\) $\mathrm{USp}(4)$ 2
12890.a.25780.1 12890.a \(y^2 + (x + 1)y = x^6 + x^5 - x^3 - x^2\) $\mathrm{USp}(4)$ 2
12949.a.12949.1 12949.a \(y^2 + y = x^5 + 2x^4 - x^3 - 2x^2\) $\mathrm{USp}(4)$ 2
12961.a.168493.1 12961.a \(y^2 + y = x^5 + 3x^4 - 5x^3 + x\) $\mathrm{USp}(4)$ 2
13078.a.26156.1 13078.a \(y^2 + xy = x^6 - 5x^5 + 7x^4 - 5x^2 + x + 1\) $\mathrm{USp}(4)$ 2
13227.a.13227.1 13227.a \(y^2 + y = x^5 - 2x^4 + 2x^3 - x\) $\mathrm{USp}(4)$ 2
13298.a.26596.1 13298.a \(y^2 + (x^3 + x)y = 2x^3 + 3x^2 + 3x + 1\) $\mathrm{USp}(4)$ 2
13418.a.26836.1 13418.a \(y^2 + (x + 1)y = -x^5 + x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 2
14067.e.126603.1 14067.e \(y^2 + y = x^5 - 3x^4 - 2x^3 + 7x^2 + 3x\) $\mathrm{USp}(4)$ 2
14138.a.28276.1 14138.a \(y^2 + (x + 1)y = x^6 - x^5 - 2x^4 + x^3 + x^2\) $\mathrm{USp}(4)$ 2
14237.a.14237.1 14237.a \(y^2 + (x^2 + x + 1)y = x^5 + x^4 - 3x^3 - x^2\) $\mathrm{USp}(4)$ 2
14481.a.43443.1 14481.a \(y^2 + y = 3x^5 - 6x^4 + 4x^3 - x\) $\mathrm{USp}(4)$ 2
14529.a.392283.1 14529.a \(y^2 + (x^3 + 1)y = x^5 + 2x^4 - 3x^2 - x\) $\mathrm{USp}(4)$ 2
14558.a.29116.1 14558.a \(y^2 + (x + 1)y = -x^5 + 2x^4 - x^3\) $\mathrm{USp}(4)$ 2
14752.a.29504.1 14752.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3 + x\) $\mathrm{USp}(4)$ 2
14890.a.29780.1 14890.a \(y^2 + (x + 1)y = x^6 + x^5 - x^4 - 2x^3\) $\mathrm{USp}(4)$ 2
14891.a.14891.1 14891.a \(y^2 + (x^2 + x + 1)y = x^5 - 3x^3 - x^2 + x\) $\mathrm{USp}(4)$ 2
14899.b.14899.1 14899.b \(y^2 + y = x^5 - x^4 - 3x^3 + 4x^2 - x\) $\mathrm{USp}(4)$ 2
14998.a.29996.1 14998.a \(y^2 + xy = x^5 - x^4 - 3x^3 + x^2 + 3x + 1\) $\mathrm{USp}(4)$ 2
15334.a.521356.1 15334.a \(y^2 + (x^3 + x^2)y = -4x^4 + 9x^3 - 9x + 4\) $\mathrm{USp}(4)$ 2
Next

Download all search results for